Brightening upconverting nanocrystals using laser-induced surface reconstruction. (December 2019) - Lei, J.; Guo, X.; Min, Q.; Yang, L.; Yang, Q.; Wang, C.; Luo, H.; Yu, X.; Qiu, J.; Zhan, Q.; Xu, X.
Abstract: Upconversion nanoparticles exhibit ordinary emission brightness for the existence of non-radiative transition induced by the surface defects, which fundamentally limits their promising applications. Here, a reconstruction process to rule out the amorphous layer and defects related to the surface of the as-synthesized particles is achieved with the use of 980-nm continuous laser irradiation. More importantly, the uniform morphology and monodispersibility of these nanoparticles are well preserved. Local heat induced via photothermal conversion of laser irradiation with the association with non-harmonic phonon coupling contributes to a tremendous improvement on the integral upconversion luminescence intensity. The upconversion intensity of Er 3+ ions in sub–10-nm Ba2 LaF7 nanoparticles enhances by more than 313-fold in the red emission, and subsequently, a bright luminescence originated from an individual particle could be observed under a multiphoton laser scanning luminescence microscopy. Our results suggest that this strategy could be extended to GdF3, KLu2 F7, and BaGdF5 systems, which exhibit drastic enhancement of emission intensity unambiguously. The laser-induced surface reconstruction in this work is demonstrated to provide a direct and facile approach to enhance the upconversion intensity, which could offer the possibility for achieving high-resolution imaging. Graphical abstract: Image 1 Highlights: High-power laser-induced surface reconstruction was achieved in 8-nm Ba2 LaF7 upconversion nanoparticles (UCNPs). Laser irradiation has a significant improvement in upconversion output. Laser-treated UCNPs could be applied to high-resolution single-particle imaging. Laser treatment has applied in fluoride matrices with various morphologies and sizes.